The aesthetic transformation of urban culture in theatrical performance manifestations (Journal of the College of Basic Education, 2023)
The theatrical show determines its position in the field of knowledge through the historical reading of cultural practice in which cultural sites turn into multiple faces of conflicts, to then create a set of contradictions between the show and the city that resolves itself in the face of the aesthetic. The city aspires to form its material models within the framework of its system. Social, conflicts with the model that the show has in the artistic system, which leads to their entry into the process of the general cultural production process. New, this is its path and its goal at the same time, but this path and this goal takes a double form, the historical and the ideological are fixed in the city and the show must establish its active and essential moment in changing the objective practices. For this, the aesthetic highlights the urban and cultural essence in order to move the subjective conditions of the city and replace them with new ones. .The research included the research problem, its importance, limits and objectives, and it included a theoretical framework that includes two chapters, the first entitled (The Architecture of the City and the Architecture of theatrical Show) and the second entitled "City Aesthetic Work in theatrical Show", then the research procedures, which included the research methodology, the research sample, the analysis of samples and the results of the research, then the conclusion of the research list of sources.